Rejang Lebong Guppy Mini Contest: An Opportunity to Teach Locals About Beautiful Ornamental Fish - Rahmadiah, Triayu; Hamka, Muhammad Subhan; Nafsiyah, Ikromatun; Al Banna, Maisya Zahra; Firman, Sri Wahyuni; Azis, Arif Rahman (Yayasan Mestika Nusantara Satu, 2024)
A small guppy ornamental fish contest was organized at the Rejang Lebong State Community College as a community service activity. The purpose of the event was to inform the public about the standards for high-quality guppies as defined by the Indonesian National Guppy Standard (SGNI) and promote the growth of ornamental fish farming in the region. The competition comprised of eight categories, encompassing contestants from both Rejang Lebong and other areas beyond the region. The implementation process consisted of several stages, namely planning, participant registration, technical setup, contest execution, exhibition and education, and evaluation. This activity effectively enhanced participants' comprehension of the attributes of high-quality guppies, methods of caring for them, and criteria for evaluating them in competitions. Furthermore, this event created prospects for economic empowerment by enhancing the value of fish sales and fostering connections among stakeholders. The assessment of the event revealed the necessity for comprehensive training and support in business management to facilitate future growth. The event showcased the capacity of instructional and competitive methods to foster community engagement and unlock the potential in ornamental fish farming.